Fuelling the future of sustainable sugar fermentation across generations. Issue 1 (10th December 2021) - Lips, David
Abstract: Biomanufacturing in the form of industrial sugar fermentation is moving beyond pharmaceuticals and biofuels into chemicals, materials, and food ingredients. As the production scale of these increasingly consumer‐facing applications expands over the next decades, considerations regarding the environmental impact of the renewable biomass feedstocks used to extract fermentable sugars will become more important. Sugars derived from first‐generation biomass in the form of, for example, corn and sugarcane are easily accessible and support high‐yield fermentation processes, but are associated with the environmental impacts of industrial agriculture, land use, and competition with other applications in food and feed. Fermentable sugars can also be extracted from second‐ and third‐generation feedstocks in the form of lignocellulose and macroalgae, respectively, potentially overcoming some of these concerns. Doing so, however, comes with various challenges, including the need for more extensive pretreatment processes and the fermentation of mixed and unconventional sugars. In this review, we provide a broad overview of these three generations of biomass feedstocks, outlining their challenges and prospects for fuelling the industrial fermentation industry throughout the 21st century.